PERSOALAN KEAGAMAAN PEREMPUAN PADA NOVEL CINTA DALAM 99 NAMA-MU KARYA ASMA NADIA - Kristiana Surya Lestari; M. Shoim Anwar (Buana Bastra, 2018)
Cinta dalam 99 Nama-Mu are interesting because they tell a girl who wants to be close to God, the character played by the main character and religious issues that occur in the main female characters. This study aims to describe more deeply the female character and religious issues that occur in the novel Cinta dalam 99 Nama-Mu by Asma Nadia, the first print of April 2018. The theory used is the theory of feminism. The main objectives to be achieved in this study, describe the character of the main character and women's religious issues in the novel Cinta dalam 99 Nama-Mu. The method used in the study is descriptive qualitative, because this research is done by reading and taking notes. The data contained in the study are written data about the elements of the story that relate to the characters and religious issues of women in the Cinta dalam 99 Nama-Mu by Asma Nadia. Data analysis used qualitative descriptive analysis, which is used to analyze the elements that build literary works from within, and look for relationships and linkages with these elements.